The effect of the essential oils from five different Lippia species on the viability of tumor cell lines - Gomide, Mayna da Silveira (2013)
Universidade Federal de Juiz de Fora. Instituto de Ciências Biológicas. Departamento de Biologia. Juiz de Fora, MG, Brazil.